Sistem Monitoring Suhu, Kelembaban, dan Ketinggian Air Pada Tanaman Hidroponik Menggunakan Raspberry Pi Berbasis IoT - Putri Ramadhanti, Fadhilah; Bintoro, Jusuf; Diamah, Aodah (JURNAL PENDIDIKAN VOKASIONAL TEKNIK ELEKTRONIKA (JVoTE), 2023)
This study aims to design an IoT-based monitoring system for temperature, humidity, and water level in hydroponic plants using Raspberry Pi, as an effort to facilitate monitoring of environmental conditions required in hydroponic plant cultivation. The research method used is Research & Development (R&D), which focuses on system design and testing. The main advantage of this system is its ability to access data in real time remotely, facilitating monitoring without having to be on site. The results of the study show that the developed monitoring system successfully sends temperature, humidity, and water level data to users with good accuracy. Therefore, it can be concluded that this IoT-based monitoring system is effective and reliable for monitoring important parameters in hydroponic plants accurately and in real time.